Genomic Landscape of Breast Cancer: Study Across Diverse Ethnic Groups - Asbiel Felipe Garibaldi-Ríos; Luis E. Figuera; Guillermo Moisés Zúñiga-González; Belinda Claudia Gómez-Meda; Ana María Puebla-Pérez; Alicia Rivera-Cameras; María Teresa Magaña-Torres; José Elías García-Ortíz; Ingrid Patricia Dávalos-Rodríguez; Mónica Alejandra Rosales-Reynoso; Patricia Montserrat García-Verdín; Irving Alejandro Carrillo-Dávila; et al. (Diseases)
Background: Breast cancer (BC) is the most common cancer among women worldwide, with incidence and mortality rates varying across ethnic groups due to sociodemographic, clinicopathological, and genomic differences. This study aimed to characterize the genomic landscape of BC in diverse ethnic groups using computational tools to explore these variations. Methodology: cBioPortal was used to analyze genomic, clinicopathological, and sociodemographic data from 1084 BC samples. Mutated genes were classified based on GeneCards platform data. Enrichment analysis was performed with CancerHallmarks, and genes not found were compared with MSigDB’s Hallmark Gene Sets. Genes absent from both were further analyzed using NDEx through Cytoscape.org to explore their role in cancer. Results: Significant differences (p < 0.05) were observed in sex, tumor subtypes, genetic ancestry, median of the fraction of the altered genome, mutation count, and mutation frequencies of genes across ethnic groups. We identified the most frequently mutated genes. Some of these genes were found to be associated with classic cancer hallmarks, such as replicative immortality, sustained proliferative signaling, and the evasion of growth suppressors. However, the exact role of some of these genes in cancer remains unclear, highlighting the need for further research to better understand their involvement in tumor biology. Conclusions: This study identified significant clinicopathological and genomic variations in BC across ethnic groups. While key genes associated with cancer hallmarks were found, the incomplete characterization of some highlights the need for further research, especially focusing on ethnic groups, to understand their role in tumor biology and improve personalized treatments.